A Rare Case of a Large Composite Endometrioma–Mature Cystic Teratoma: The Importance of Surgical Treatment and Pathologic Diagnosis - Jun Song; Caitlin Martin (Reproductive Medicine)
Endometriosis is a common benign gynecologic disorder associated with infertility and pelvic pain, affecting 6–11% of reproductive-age females, and can frequently lead to the formation of ovarian endometriomas. Mature cystic teratomas are benign ovarian tumors comprising 10–25% of ovarian tumors. Both pathologies are common individually but rarely coexist. The case presented here describes a 49-year-old female presenting with a large composite endometrioma–mature cystic teratoma, a rare occurrence with few documented cases. The patient had a 24 cm × 17 cm × 15 cm adnexal mass identified via imaging, which was surgically removed. Pathology confirmed a composite tumor, with the teratoma encased within the endometrioma. This case underscores the importance of surgical management in complex adnexal masses to obtain tissue for definitive diagnosis and to exclude malignancy. Given the rarity of such coexistence and the challenges in preoperative diagnosis, surgical intervention is crucial for accurate diagnosis and effective management.